Association between temporomandibular disorder and condylar position in a university population - Anderson Vilchez-Chavez; Augusto Aguirre-Aguilar; Marcos J. Carruitero (Universidad de Concepción., 2021)
Aim: To determine the association between the level of temporomandibular disorder (TMD) and the condylar position in a university population. Material and Methods: A cross-sectional study was carried out in 41 university students between 18 and 27 years old (21±2.28). The level of TMD was determined using the Helkimo index modified by Maglione, whereas the condylar position was found radiographically by lateral scan. The association was evaluated using the Chi-square statistical test. Results: Statistically significant association was found between the TMD level and the condylar position in the female gender (p=0.003). The central condylar position was the most frequent in females (70.00%), while in males the highest frequency of condylar positions was posterior and anterior, 40.48% and 35.71% respectively. In mild TMD, the most frequent condylar position was central (46.34%), whilst non-centric positions were prevalent in moderate TMD, with 2.44%. There was no statistically significant association between the TMD level and the condylar position of the participants, nor in males (p>0.05). Conclusion: The TMD was associated with the condylar position in females of the university population studied, analyzed in lateral temporomandibular joint scans. Non-centric condylar positions were more frequent in the moderate TMD level and centric positions in mild TMD